Answer:
1). y= -5+3x
2). y= -2x-13
3). y= -6x+2
4). y= -x+4
5). y≈ 0.57x
6). y=2x-9
7). Equation incomplete
8). y=3x+23
Step-by-step explanation:
1).
3x-y=5
<em>Subtract 3x from both sides</em>
-y=5-3x
<em>Multiply both sides by -1</em>
y= -5+3x
2).
y+7= -2(x+3)
y+7= -2x-6
<em>Subtract 7 from both sides</em>
y= -2x-13
3).
y= -10-6(x-2)
y= -10-6x+12
y= -6x+2
4).
3x=12-3y
<em>Add 3y to both sides</em>
3x+3y=12
<em>Subtract 3x from both sides</em>
3y=12-3x
<em>Divide both sides by 3</em>
y= -x+4
5).
-4x-7y=0
<em>Add 4x to both sides</em>
-7y= -4x+0
<em>Multiply both sides by -1</em>
7y= 4x
<em>Divide both sides by 7</em>
y≈ 0.57x
6).
4x-2y=18
<em>Subtract 4x from both sides</em>
-2y= -4x+18
<em>Multiply both sides by -1</em>
2y=4x-18
<em>Divide both sides by 2</em>
y=2x-9
7).
y= 5-
Equation is incomplete.
8).
y-2=3(x+7)
y-2=3x+21
<em>Add 2 to both sides</em>
y=3x+23